”Hvad laver en festivalarrangør om vinteren?” - Thiesen, Lene (Peripeti, 2022)
“What does a festival producer do during winter?” In this essay, Lene Thiesen offers insights into the job of festival programming in Copenhagen International Theatre (KIT) in the years from 1983 to 1997. Providing a perspective from inside the organization, it touches upon the lack of cultural political support for international exchanges, which was luckily outweighed by the enthusiasm of the artists, the volunteers, the audience, and the press. It also tracks the shifts in KIT’s artistic profile from the street theatre of the Fools Festivals through the thematized bilateral festivals with French and British artists, to the Dancin’ City and Images of Africa festivals in the mid-1990s.